2016
DOI: 10.1039/c5nj02544c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (Ag,F)-modified anatase TiO2 nanosheets and their enhanced photocatalytic activity

Abstract: The strong interactions between Ag nanoparticles and TiO2 nanosheets can improve the photocatalytic activity of TiO2 nanosheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It was confirmed that Ag was effectively deposited on the surface of TiO 2 nanopowder. Specifically, Ag + ions were adsorbed onto the crystal structure of TiO 2 and subsequently formed Ag-TiO 2 [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…It was confirmed that Ag was effectively deposited on the surface of TiO 2 nanopowder. Specifically, Ag + ions were adsorbed onto the crystal structure of TiO 2 and subsequently formed Ag-TiO 2 [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Although the chemical constitutions in the series of as-prepared Ag/TiO 2 composites are expected to be similar, their colors are significantly different from each other in indoor natural light (Figure ), and presumably depend on the LSPR effect that is related to the chemical surroundings of Ag NPs and the interface interactions between a-TiO 2 and Ag NPs. , To rationalize the observation, the contents of organic residues and Ag metal on Ag/TiO 2 composites were, respectively, analyzed by TGA, Fourier transform infrared spectroscopy (FT-IR), and ICP-MS techniques. In each TGA curve (Figure A), there is a significant mass loss at about 273 °C.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the resonance frequency of LSPR strongly depends on the particle size, shape, composition, refractive index of the surrounding medium, and interparticle spacing. ,, Hence, the LSPR-induced rate enhancements in the composite photocatalysis depend on the geometric arrangements of noble-metal NPs and semiconductor in addition to their optical properties. Several strategies have been developed to synthesize the composite photocatalysts, including chemical reduction, light-induced reduction, photodeposition, thermal decomposition, liquid impregnation, sol–gel, or hydrothermal method. ,, To obtain plasmonic-metal/semiconductor composites with a high photocatalytic activity, however, there are still great challenges in the controlled synthesis of the composites in which the building blocks are suitably arranged and critically separated by nonconductive organics with optimal spacing to depress the decay process of irradiation energy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation